Surrogate-model-based calibration of effective transport parameters from push-pull tests in the Horonobe aquifer (Japan) - Elena Petrova; Philipp Selzer; Stefan Kranz; Sarah Zeilfelder; Klaus H. Hebig; Isao Machida; Atsunao Marui; Guido Blöcher; Traugott Scheytt (Geothermics, 2025)

Identification of modern meteoric water, glacial meteoric water, and fossil seawater in a deep borehole at the coastal area of Horonobe, north Japan, using groundwater dating and paleoclimatic proxy methods - Takuma Hasegawa; Kotaro Nakata; Yuichi Tomioka; Tomoko Ohta; Shunichi Okamoto; Atsunao Marui; Isao Machida; Reo Ikawa; Masahiko Ono; Shinji Matsumoto (Chemical Geology, 2024)

Deciphering natural and anthropogenic effects on the groundwater chemistry of Nago City, Okinawa Island, Japan - Naoyuki Yoshihara; Shinji Matsumoto; Isao Machida; Youhei Uchida (Environmental Pollution, 2023)

Applicability of d-excess and 17O-excess as groundwater tracers for determination of recharge area - Isao Machida; Masahiko Ono; Takafumi Kamitani; Yasuhide Muranaka (Hydrogeology Journal, 2022)
Methods to determine the recharge elevation of groundwater using the altitude effect of δD and δ 18 O have been extensively applied in hydrogeological investigations. The secondary parameter d-excess has also been used as a groundwater tracer. In this study, to examine the usefulness of these tracers along with 17 O-excess, ~160 groundwater samples were collected from a humid region at the foot of Mt. Fuji, Japan. The sampling area covered 40 × 45 km, with most sampling sites located below 1,000 m above sea level. The relatively low elevation and small scale of the basin allowed for examination of the elevation-dependence of groundwater isotopes. Using high-precision isotope analyses, a low lapse rate but clear elevation-dependence in spring waters was observed for d-excess (0.18‰·100 m −1 ). The recharge elevation determined by d-excess correlated with those by δD and δ 18 O, indicating that d-excess has high potential as a groundwater tracer for the determination of recharge elevation. On the other hand, 17 O-excess in groundwater held small spatial variation, with an average of 25 per meg in the horizontal direction and a lapse rate of 0.6 per meg·100 m −1 . The low lapse rate compared to the analysis error inhibits its usefulness as a tracer. The fact that the recharge elevation determined by δD, δ 18 O, and d-excess were similar indicates that the combination of these tracers could increase the reliability of the results.

Construction of a conceptual model for confined groundwater flow in the Gunii Khooloi Basin, Southern Gobi Region, Mongolia - Batdemberel Bayanzul; Kengo Nakamura; Isao Machida; Noriaki Watanabe; Takeshi Komai (Hydrogeology Journal, 2019)

Regional groundwater flow system in a stratovolcano adjacent to a coastal area: a case study of Mt. Fuji and Suruga Bay, Japan - Masahiko Ono; Isao Machida; Reo Ikawa; Takafumi Kamitani; Koichi Oyama; Yasuhide Muranaka; Akira Ito; Atsunao Marui (Hydrogeology Journal, 2019)

Coastal aquifer system in late Pleistocene to Holocene deposits at Horonobe in Hokkaido, Japan - Reo Ikawa; Isao Machida; Masaru Koshigai; Seiji Nishizaki; Atsunao Marui (Hydrogeology Journal, 2014)

Carbon-14 age and chemical evolution of Ca(HCO3)2-type groundwater of age less than 8,000 years in a confined sandy and muddy Pleistocene aquifer, Japan - Isao Machida; Yohey Suzuki; Mio Takeuchi (Hydrogeology Journal, 2013)

Evidence for the grazing hypothesis: Grazing reduces phytoplankton responses of the HNLC ecosystem to iron enrichment in the western subarctic pacific (SEEDS II) - Atsushi Tsuda; Shigenobu Takeda; Hiroaki Saito; Jun Nishioka; Isao Kudo; Yukihiro Nojiri; Koji Suzuki; Mitsuo Uematsu; Mark L. Wells; Daisuke Tsumune; Takeshi Yoshimura; Tatsuo Aono; et al. (Journal of Oceanography, 2007)

Geochemical Changes in Spring Water Associated with the 2000 Eruption of the Miyakejima Volcano, Japan - Tsutomu Sato; Isao Machida; Makoto Takahashi; Taro Nakamura (Pure and Applied Geophysics, 2006)